Modelling the ageing behaviour of supercapacitors using electrochemical impedance spectroscopy for dynamic applications - Mohammad Naim, Nur Nafisah (2015)
Diagnosis of ageing mechanisms in supercapacitors is made difficult by the enforcement of various ageing factors in the current ageing tests. The thesis presents the exact determination of the ageing mechanism by separating the impacts of high temperature, current cycling and constant voltage applications in accelerated ageing tests. The state of health (SOH) of the supercapacitors are monitored periodically with electrochemical impedance spectroscopy, cyclic voltammetry and constant current test to observe the evolution of ageing.